Kajian Pemanfaatan Buah Edibel Suku Dayak Banyadu Di Hutan Tembawang Desa Setia Jaya Kecamatan Teriak Kabupaten Bengkayang - Irwan Lovadi, Tri Esti Kurniawati, Masnur Turnip, (Universitas Tanjungpura, 2015)
Dayak Banyadu tribe were people who live in Setia Jaya Village, sub-district of Teriak in Bengkayang Regency. Dayak Banyadu settlements in Bengkayang Regency scattered in several places, one of them was in forest area of Tembawang, Setia Jaya Vllage, Sub-district of Teriak. Setia Jaya Village communities stillused forest plant fruits that can be consumed to meet their needs of fruits. The study aimed to determine the type, use and processing of edibel by Dayak Banyadu tribe community in Setia Jaya Village, sub-distric of Teriak, Bengkayang Regency. This study was conducted over three months from May to August 2014. In collecting data, survey method and semi-structured interviews were applied and the data were presented descriptively. To recruit respondents, purposive sampling method was applied and 15 people were willing to involve. The result showed that 25 species of edibel belonging to 15 families consumed by villages of Setia Jaya. The most widely consumed fruit comes from the family of Moraceae by 5 species and 25 species of fruit, particularly their pulp were the most widely consumed. Counsuming the fruits directly was the most favourite way among the villagers